2021
DOI: 10.3390/jof7040255
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine for the Treatment of Fusarium Keratitis: A Case Series and Mini Review

Abstract: Fungal keratitis is difficult to treat, especially Fusarium keratitis. In vitro studies show that chlorhexidine could be an interesting option as monotherapy. We describe a case series of four patients (four eyes) with Fusarium keratitis at Radboud University Medical Center (Nijmegen, the Netherlands). The patients were treated with chlorhexidine 0.02% eye drops. The in vitro activity of eight antifungals and chlorhexidine was determined according to the European Committee on Antimicrobial Susceptibility Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The fungicidal activity of other tested substances was lower than activity of CHX. As proof of the clinical significance of the above mentioned results, Oliveira dos Santos et al published a case series of four patients with culture proven Fusarium keratitis, with small infiltrates that were successfully treated with 0.02% CHX alone [ 102 ]. The study showed good susceptibility of the isolated Fusarium strains to CHX as well as the high CHX fungicidal effect.…”
Section: Antisepticsmentioning
confidence: 99%
“…The fungicidal activity of other tested substances was lower than activity of CHX. As proof of the clinical significance of the above mentioned results, Oliveira dos Santos et al published a case series of four patients with culture proven Fusarium keratitis, with small infiltrates that were successfully treated with 0.02% CHX alone [ 102 ]. The study showed good susceptibility of the isolated Fusarium strains to CHX as well as the high CHX fungicidal effect.…”
Section: Antisepticsmentioning
confidence: 99%
“…The chlorhexidine MICs of all isolates of P. boydi tested were 0.008 μg/ml. Four patients with Fusarium keratitis were successfully treated with chlorhexidine 0.02% eye drops by Oliveira dos Santos et al [24]. The efficacy of chlorhexidine for treating fungal keratitis has been confirmed by studies [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…Four patients with Fusarium keratitis were successfully treated with chlorhexidine 0.02% eye drops by Oliveira dos Santos et al [24]. The efficacy of chlorhexidine for treating fungal keratitis has been confirmed by studies [24,25]. There is a need for further research on the use of chlorhexidine in Pseudallescheria keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent case series from the Netherlands also reported MICs isolates from four patients with FK (all Fusarium spp ) as ranging from 2 to 32 mg/L. 31 The Mycotic Treatment Trial I (MUTT I) also reported the MICs of natamycin for the 256 patients who had fungal culture results. 32 The reported natamycin MIC ranged from 2 to 32 mg/L for Fusarium spp and from 8 to 64 mg/L for Aspergillus flavus .…”
Section: Discussionmentioning
confidence: 99%